Improving the mathematical models applied for the sollution of solid assembly constructions thermoelasticity problem - Morhun, S.A. (Проблемы машиностроения, 2017)
The problem of sleeve and shaft assemblies finite elements models development has been studied. All calculations have been provided for the assemblies that are widely spread in the power-plant engineering and marine engine building. The matter is that such details have constructional non-homogeneity, which hardly ever could be correctly explained, using well-known finite elements and their mathematical dependences. On the other hand, the mathematical model should be as simple as possible for the purpose of its wide usage in the process of assembly’s design. That is why the new finite elements model, which consists of three-dimensional isoparametric finite elements, has been developed. It has been used for the calculation of displacement, caused by complex influence of heat flux and contact load. Such approach gives an opportunity to describe the whole assembly as the superposition of the developed sleeve and shaft finite elements models and make the process of calculation more correct and even compact. All calculations of displacement and temperature fields have been held for two widely spread conjugation types, that are used for such assemblies creation. Изложена методика построения уточненной конечно-элементной модели сборочных конструкций типа «вал» − «втулка», имеющих значительное распространение в энергомашиностроении. С использованием разработанных трехмерных конечных элементов решена контактная термоупругая задача для данного типа соединений. Получено поле распределения перемещений на торцевых поверхностях вала и втулки, а также поле распределения температур в соединении. Викладено методику побудови уточненої скінченно-елементної математичної моделі збірних конструкцій типу «вал» − «втулка», що мають значне розповсюдження в енергомашинобудуванні. З використанням розроблених тривимірних скінченних елементів розв’язано контактну термопружну задачу для даного типу з’єднань. Отримано поле розподілу переміщень на торцевих контактуючих поверхнях валу та втулки, а також поле розподілу температур в з’єднанні